Exploring boundary violations between staff and clients in healthcare and forensic settings - Britton, Emma (2016)
Thesis Aim: Boundary violations are committed when a professional crosses the emotional, physical, spiritual or sexual limits of another, thus disrupting the relationship between staff and clients. This thesis explores this issue in the context of healthcare and forensic settings. It identifies boundary violation risk and protective factors for staff working with forensic healthcare patients. The thesis also investigates reasons why staff under-report and may not whistleblow their concerns in these areas.